La cooperación descentralizada como eje articulador del crecimiento económico en las regiones colombianas (2016)
In search of tools and mechanisms to achieve high levels of economic growth, regions and territories explore options among which are among other international cooperation, beyond the recipient donor relationship, according to the principal of shared responsibility and in specifically in the form of decentralized cooperation that can bring sub-national entities such as municipalities in different countries to solve particular situations identified by the communities themselves, contributing for example to produce better conditions, but also with a higher level of ownership, which not only it makes them more competitive in the markets, but allows them to have among others, better trading conditions and access to financial and technical resources, to generate more revenue, improve existing living conditions and increase economic growth. lt's a bit the perception that aims embodied here to sensitize and potentiate its use in the Colombian regions.